Sex difference in incidence of gastric cancer: an international comparative study based on the Global Burden of Disease Study 2017 - Lixia Lou; Linyan Wang; Yaoyi Zhang; Guofeng Chen; Lele Lin; Xiaoli Jin; Yi Huang (BMJ Open)
Objectives To investigate sex difference in global gastric cancer incidence by year, age and socioeconomical status.Design An international comparative study.Setting We obtained the global and national sex-specific incidence of gastric caner by year and age from the Global Burden of Disease Study 2017. The human development index (HDI) in 2017 as an indicator of national socioeconomical status was extracted from the Human Development Report.Main outcome measures Sex-specific incidence of gastric cancer was compared by year and age at the global level. Linear regression analyses were performed to explore socioeconomic-associated sex difference in gastric cancer incidence.Results Despite declining incidence of global gastric cancer in both sexes between 1990 and 2017, relative sex difference showed an increasing trend, with male to female ratios of age-standardised incidence rates (ASRs) rising from 1.86 to 2.20. Sex difference was almost negligible under 45 years of age and relative difference maximised in the age range of 65–69 years with male to female ratios of ASRs being 2.74. Both absolute sex difference (standardised β=0.256, p<0.001) and relative difference (standardised β=0.387, p<0.001) in ASRs were positively associated with HDI.Conclusions This study revealed that decreasing incidence of global gastric cancer was accompanied by widening sex difference in the past few decades. Men always had higher incidence than women. Greater sex difference was found in older age and in more developed countries. These findings highlight the importance of making sex-sensitive health policy to cope with the global gastric cancer burden.